Critical Analysis of the Efficacy and Limitations of GLP-1 Pharmaceuticals in Obesity Management: A Comprehensive Literature Review - Gierlach, Katarzyna; Nowak, Karolina; Nowak, Karolina; Olejarz, Zuzanna; Słowik, Magdalena; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Nieć, Maria; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Obesity, a pervasive global pandemic intricately linked to various comorbidities, necessitates a comprehensive and nuanced approach. This article delves into the intricate realm of obesity guidelines, underscoring the significance of lifestyle modifications, preventive measures for childhood obesity, population-based strategies, clinical management protocols, and vigilant monitoring. GLP-1 drugs, originally designed for type 2 diabetes management, exhibit multifaceted effects beyond glycemic control. They influence appetite regulation, gastric emptying dynamics, and potentially contribute to cardiovascular health improvements. However, the commendable effects come with a caveat - potential side effects necessitating careful consideration in clinical decision-making. Despite gaining popularity through celebrity endorsements, this article firmly underscores the need to view GLP-1 pharmacotherapy as a recommended intervention rather than a miraculous solution. A brief description of the state of knowledge Integral to the obesity discourse is the imperative to address weight stigma, demanding evidence-based approaches in both clinical and public health domains. The narrative extends into the future landscape of obesity pharmacotherapy, contemplating the potential role of probiotics. Emphasizing the necessity for long-term studies and randomized trials, it positions probiotics as a low-risk alternative with significant potential in mitigating obesity while simultaneously addressing concerns related to antibiotic resistance. Summary The pursuit of a balanced and effective approach to obesity management necessitates a nuanced understanding of medical interventions, consideration of societal perceptions, and exploration of innovative possibilities within the evolving landscape of healthcare.